The development of global education in Malaysia: Strategies for internationalization - Mohamad, Mohamad Hanapi; Ghazali, Zahiruddin (Palgrave Macmillan, 2003)
The globalization of society and the economy has had an impact on research and education and been influenced by them.In the case of Malaysia, a liberalized democratic education policy brought a sudden upsurge of foreign students to Malaysia in 1966, when the government introduced the Higher Education Act. Terms such as international education and global education were an expression of this development. To become a major player, however, Malaysia essentially needs to acquire global competencies, in curriculum, administrative ease or pricing, in order to make its location a strategic choice for post-secondary education. The globalization of markets and competition, rapid technological changes and changing relationships between states and firms require different approaches from those traditionally assumed.This chapter proposes the development of a coherent global education model of higher education, based on an eclectic-locational rather than a multidisciplinary approach.